PENERAPAN PENDIDIKAN AGAMA KRISTEN BERBASIS KONTEKSTUAL TERHADAP KEHIDUPAN PERIBADAHAN - PERMADI, YOAS BRATA; JUNTAK, JUSTIN NIAGA SIMAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
Church is a life together in one community, where in one community there are characteristics that are owned and of course with all the strengths and challenges that are owned. GKJ Jambeyan is a rural church in the Sragen area of ??Central Java, where the community is still very traditional and prioritizes local culture, namely Javanese culture, which is an element that binds their fellowship. In the midst of this fellowship, there is a problem, namely that there are some people who feel that they do not fit in with the service pattern applied by the church, where the church is considered old-fashioned and does not adapt to the conditions of the times so that some decide not to worship at GKJ Jambeyan anymore. The formulation of the problem to be raised is first, how is the implementation of contextual-based Christian religious education in GKJ Jambeyan? Second, what is the impact of the implementation of contextual-based Christian religious education on the worship life of the congregation at GKJ Jambeyan? The objectives of the study are expressed as follows: First, to analyze the implementation of contextual-based Christian religious education in GKJ Jambeyan. Second, to examine the impact of the implementation of contextual-based Christian religious education on the worship life of the congregation at GKJ Jambeyan. The research method used is descriptive qualitative. The results of this study reveal that Javanese culture, which is the result of contextualization, is a force that must be developed because it is a bond of fellowship. ABSTRAKGereja adalah kehidupan bersama dalam satu komunitas, dimana dalam satu komunitas ada ciri khas yang dimiliki dan tentunya dengan segenap kekuatan dan tantangan yang dimiliki. GKJ Jambeyan adalah gereja pedesaan di daerah Sragen Jawa Tengah, dimana masyakaratnya masih sangat tradisional dan mengedepankan budaya local yaitu budaya Jawa yang menjadi unsur pengikat persekutuan mereka. Di tengah-tengah persekutuan itu ada persoalan yaitu ada beberapa orang yang merasa tidak cocok dengan pola pelayanan yang diterapkan oleh gereja, dimana gereja dianggap kolot dan tidak menyesuaikan keadaan jaman sehingga ada yang memutuskan tidak beribadah lagi di GKJ Jambeyan. Ada pun rumusan masalah yang hendak diangkat adalah pertama, bagaimana penerapan pendidikan agama Kristen berbasis kontekstual di GKJ Jambeyan? Kedua, bagaimana dampak penerapan pendidikan agama Kristen berbasis kontekstual terhadap kehidupan peribadahan jemaat di GKJ Jambeyan? Ada pun tujuan penelitian diungkapkan sebagai berikut: Pertama, menganalisis penerapan pendidikan agama Kristen berbasis kontekstual di GKJ Jambeyan. Kedua, mengkaji dampak penerapan pendidikan agama Kristen berbasis kontekstual terhadap kehidupan peribadahan jemaat di GKJ Jambeyan. Metode penelitian yang dipakai adalah deskriptif kualitatif. Hasil penelitian ini mengungkapkan bahwa budaya Jawa yang merupakan hasil kontekstualisasi menjadi kekuatan yang harus dikembangkan karena sebagai pengikat persekutuan.